The recommendations of using incorporating climate change issues into educational curricula - Hadi, Assel Amer; Fadhil, Nada Allawi; Saleem, Hanan Kareem; Jebril, Nadia Mahmoud Tawfiq; Hamzah, Sarah Hussein; Jebril, Lina Mahmoud Tawfiq (Tasnim International Journal for Human, Social and Legal Sciences, 2024)
Climate change represented by an increase in the average temperature beyond 1.5°C is a global problem in nature, so this topic must be engaged in interpretation as part of instruction and exploration in educational curricula (educational institutions and universities). Climate change education (CCE) is a critical retort to this issue. The 2020 Global Education Monitoring Report by UNESCO accentuates the impression of instruction on both environment modification vindication and revision, but despite this, numerous nations do not distinguish the standing of climate change education and do not invest significantly in it. Therefore, this review highlights the role of environment transformation tutoring in the education sector and provides solutions to the challenge of expanding climate change education by giving examples of how this can be integrated into every discipline in graduate school and academies.